Valuation and importance of the extrinsic attributes of the product from the firms´ perspective in a Spanish wine protected designation of origin - Garcia-Galan, M. Mar; del Moral-Agúndez, Alejandro; Galera-Casquet, Clementina (Spanish Journal of Agricultural Research, 2014)
Designations of origin (DOs) are commercial brands of wide use in the agro-food sector. Its use in Spain has taken place for more than three decades and although wineries managers have incorporated these new forms of protection, little is known about their opinion and their point of view during the DO implementation process. In fact, the consumers’ point of view has been the one most often analyzed in the literature. In the present study we analyzed extrinsic attributes of a wine with DO from the company point of view. In particular, we analyzed brand, product, price, packaging and label, and origin of the product following a qualitative analysis on interviews carried out with winemakers of the DO wine Ribera del Guadiana during the last decade. The qualitative analysis of the interviews was performed using the software package ATLAS/ti, designed for this type of data analysis in the form of large blocks of text. The results indicated that winemakers consider that they offer a good product to the market, and try to promote their brands using the origin of the product as a marketing strategy. From the company point of view, this protected DO (PDO) has important opportunities for positioning to create a sustainable competitive advantage, focusing on quality and the territorial differentiation.